2021
DOI: 10.1093/tbm/ibab017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tailoring on weight loss among young adults receiving digital interventions: an 18 month randomized controlled trial

Abstract: Weight loss outcomes among young adults in technology-based programs have been equivocal. The purpose of this study was to deliver digital weight loss treatments to young adults and examine the 6, 12, and 18 month effects on weight loss. Young adults with overweight/obesity (N = 459; 23.3 ± 4.4 years) were recruited from two university sites and randomly assigned to receive through Facebook and text messaging either personalized (TAILORED; n = 150) or generic (TARGETED; n = 152) weight loss information, messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…At 6 months, there was no overall effect of study group for weight loss. There was a moderating effect such that among those with the lowest BMIs (25–27.5 kg/m 2 ), participants who were assigned to the tailored group lost 2.7 kg [−3.86, −0.68] and those in the targeted group lost 1.72 kg [−3.16, −0.29] more than those in the control group after adjustment for covariates [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…At 6 months, there was no overall effect of study group for weight loss. There was a moderating effect such that among those with the lowest BMIs (25–27.5 kg/m 2 ), participants who were assigned to the tailored group lost 2.7 kg [−3.86, −0.68] and those in the targeted group lost 1.72 kg [−3.16, −0.29] more than those in the control group after adjustment for covariates [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Students were excluded if they had medical conditions that could affect study outcomes, safety, or weight loss, including medications for diabetes, steroids, or unstable medication dosage (<3 months). See Napolitano et al, (2017) for full inclusion and exclusion criteria and Napolitano et al, (2021) for full consort diagram of participant enrollment numbers. Only participants with full data ( n = 397) were included in the analytic sample.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis will use data from the Healthy Body Healthy U (HBHU) study conducted at the George Washington University (GWU) and the University of Massachusetts-Boston (UMB) in the United States [ 17 ]. This 18-month randomized, controlled clinical trial examined the efficacy of two social media-based interventions for weight loss among young adults ages 18–35 years attending a college or university in Washington, DC or Boston [ 18 ]. The two interventions were compared to a contact control group, and all were delivered via Facebook and SMS text messaging.…”
Section: Methodsmentioning
confidence: 99%
“…The Tailored and Targeted study arms will be included because their primary outcome is weight loss [ 17 ]. Study outcomes are reported elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%